Evaluation of a peri-urban smallholder farmers’ soil amendment practices on soil quality and crop growth, yield and quality - Gobozi, Thamsanqa Khanya Sikho (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.